1999
DOI: 10.1039/a808507b
|View full text |Cite
|
Sign up to set email alerts
|

Modification by lanthanide (La, Ce) promotion of catalytic properties of palladium: Characterization of the catalysts

Abstract: catalysts modiÐed by cerium or lanthanum oxide were prepared according to a standard Pd/c-Al 2 O 3 procedure. The nature of the interaction between the metallic particles and the promoted support was addressed. The e †ects of changing the following parameters were studied : (i) precursor palladium salt (chloride or nitrate), (ii) content of lanthanide (from the unpromoted catalyst to the pure lanthanide oxide) and (iii) nature of the lanthanide (La or Ce). This paper focuses on the study of the transition meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…A similar result was observed with PtSn/γ -Al 2 O 3 -La catalysts prepared by coimpregnation [15]. It has been reported that lanthanides have the ability to retain chlorine on the surface [19,20].…”
Section: Catalysts Characterizationsupporting
confidence: 72%
“…A similar result was observed with PtSn/γ -Al 2 O 3 -La catalysts prepared by coimpregnation [15]. It has been reported that lanthanides have the ability to retain chlorine on the surface [19,20].…”
Section: Catalysts Characterizationsupporting
confidence: 72%
“…The ratio of the band areas due to metallic palladium as compared to the sum of the band areas due to metallic and oxidized palladium is 0.44, suggesting that approximately 44% of palladium present is in metallic form. It must be noted that although palladium is reduced by hydrogen at 200°C, upon exposure to air, the palladium can be re-oxidized [34]. This likely occurred for this system, as samples were stored under ambient conditions after treatment.…”
Section: Resultsmentioning
confidence: 97%
“…The interfacial polarization resistance R p of the bare gold electrode used as anode resulted 4,220 Ω·cm [4]. This catalytic behaviour might be explained by an high H 2 consumption creating new active sites through hydrogen or oxygen spillover [4,29]. Even more evident effect was noticed by evaluating the catalytic activity of the novel material cathodic catalyst.…”
Section: Single Cell Testing-electrochemical Impedance Spectrometrymentioning
confidence: 88%